Local Media Policy in Countering Hoaxes for the 2024 Elections - Pramesti, Olivia Lewi; Andreas Tri Pamungkas (Jurnal ILMU KOMUNIKASI, 2025)
The spread of hoaxes is one of the challenges of the 2024 elections, as they can disrupt public trust in candidates. This research compares local media policies in countering hoaxes during the 2024 elections. Local media play an important role in democratization, but often it is trapped as a political agent. This research uses in-depth interviews with editorial boards of local media across Java Island. The results show that local media generally lack specific policies to counter hoaxes. The economic challenges faced by local media influence their policy to counter hoaxes for the 2024 elections.